2012
DOI: 10.1007/s00415-011-6336-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of upper limb apraxia

Abstract: Upper limb apraxia, a disorder of higher motor cognition, is a common consequence of left-hemispheric stroke. Contrary to common assumption, apraxic deficits not only manifest themselves during clinical testing but also have delirious effects on the patients’ everyday life and rehabilitation. Thus, a reliable diagnosis and efficient treatment of upper limb apraxia is important to improve the patients’ prognosis after stroke. Nevertheless, to date, upper limb apraxia is still an underdiagnosed and ill-treated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 69 publications
(153 reference statements)
1
68
0
8
Order By: Relevance
“…462 Two reviews concluded that there was not enough information to determine whether interventions for apraxia were efficacious. 458,459 Some studies have found immediate postintervention improvements on apraxia tests or in daily life activities, but few have found lasting advantages for the trained groups.…”
Section: Limb Apraxiamentioning
confidence: 99%
“…462 Two reviews concluded that there was not enough information to determine whether interventions for apraxia were efficacious. 458,459 Some studies have found immediate postintervention improvements on apraxia tests or in daily life activities, but few have found lasting advantages for the trained groups.…”
Section: Limb Apraxiamentioning
confidence: 99%
“…The findings of the current study have important implications for the development of novel treatment strategies of apraxia (Buxbaum et al, 2008;Dovern et al, 2011). The data suggest that such strategies should include incidental motor learning and thereby make use of the remaining motor learning resources of patients with apraxia.…”
Section: Discussionmentioning
confidence: 60%
“…Definitions and taxonomies of apraxia and its subcomponents are diverse and competing cognitive models disagree in the definition of domains that essentially constitute the syndrome 2 3. However, dysfunctions in imitation and pantomime on command have been proposed as the core features of the syndrome 4.…”
Section: Introductionmentioning
confidence: 99%
“…However, dysfunctions in imitation and pantomime on command have been proposed as the core features of the syndrome 4. This descriptive division of praxis domains and subdomains (figure 1) has overcome a range of definitional and practical issues in apraxia research and has thus been adopted by modern apraxia screening tests for patients with stroke 2 3…”
Section: Introductionmentioning
confidence: 99%